2011
DOI: 10.1128/jb.00005-11
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extension of Slipped DNA Intermediates by DinB Is Required To Escape Primer Template Realignment by DnaQ

Abstract: We show that Escherichia coli DinB polymerase, which creates single-base deletions, prefers to extend slipped DNA substrates with the skipped base at the ؊4 position. A DinB(Y79L) variant, which extends these substrates less efficiently in vitro, allows the proofreading function of polymerase III to reverse their formation in vivo.The Y family of DNA polymerases catalyze replication on damaged DNA templates in a process called translesion DNA synthesis (TLS), which allows cells to tolerate DNA damage (7). Memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…An unpaired base at the −2 position is used ∼10-fold less efficiently than at the −3 position, with a k obs of 0.38 ± 0.04 s − 1 , suggesting that proximity to the active site reduces tolerance for an extrahelical nucleotide. This preference for an unpaired base further away from the active site has been observed for other DinB polymerases as well (27,28,30). …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…An unpaired base at the −2 position is used ∼10-fold less efficiently than at the −3 position, with a k obs of 0.38 ± 0.04 s − 1 , suggesting that proximity to the active site reduces tolerance for an extrahelical nucleotide. This preference for an unpaired base further away from the active site has been observed for other DinB polymerases as well (27,28,30). …”
Section: Resultssupporting
confidence: 72%
“…Having already ruled out misincorporation-misalignment for the 4C-G template, we used these altered substrates to distinguish template slippage from dNTP-stabilized misalignment. Similar DNA substrates have been used to assess deletion mechanisms for other DinB polymerases (27,28,30). …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, when the TLS patch is !5 nucleotides long, Pol III extends the primer and thus successfully completes the TLS pathway. Similarly, Walker and colleagues observed that efficient bypass of an N 2 -furfuryl-guanine adduct by Pol IV requires both insertion across the lesion and subsequent extension by at least four bases to prevent degradation by proofreading (Jarosz et al 2009;Foti and Walker 2011). It should thus be stressed that the most important factor that determines success or failure of a TLS pathway resides in the length of the TLS patch given that polymerase is able to synthesize under single-hit conditions.…”
Section: In 2009 Goodman and Woodgate Reportedmentioning
confidence: 99%
“…DNA polymerase IV uses a template slippage mechanism to create single base deletions on homopolymeric runs [35]. DNA polymerase IV, which creates single-base deletions, prefers to extend slipped DNA substrates with the skipped base at the −4 position [36]. Overexpression of enzymes of the base excision repair pathway is known to increase the frequency of frameshift mutations [37].…”
Section: Introductionmentioning
confidence: 99%